Harnessing nanostructured systems for improved treatment and prevention of HIV disease. Issue 2 (27th July 2018) - Monroe, Maya; Flexner, Charles; Cui, Honggang
Abstract: Combination antiretroviral therapy effectively controls human immunodeficiency virus (HIV) viral replication, delaying the progression to acquired immune deficiency syndrome and improving and extending quality of life of patients. However, the inability of antiretroviral therapeutics to target latent virus and their poor penetration of viral reserve tissues result in the need for continued treatment for the life of the patient. Side effects from long‐term antiretroviral use and the development of drug resistance due to patient noncompliance are also continuing problems. Nanostructured systems of antiretroviral therapeutics have the potential to improve targeted delivery to viral reservoirs, reduce drug toxicity, and increase dosing intervals, thereby improving treatment outcomes and enhancing patient adherence. Despite these advantages, very few nanostructured antiretroviral delivery systems have made it to clinical trials due to challenges in preclinical and clinical development. In this context, we review the current challenges in HIV disease management, and the recent progress in leveraging the unique performance of nanostructured systems in therapeutic delivery for improved treatment and prevention of this incurable human disease.